Green Premium: What is the Implied Prognosis for Sustainability?. Issue 1 (1st January 2020) - Addae-Dapaah, Kwame; Wilkinson, Jamie
Abstract: Economic considerations underpin almost every decision to determine social priorities. It is not surprising then that sustainability has fast become, among other things, economic advocacy. This has led to a proliferation of studies to establish the provenance of a green premium to provide impetus for sustainable real estate development to drive the sustainability agenda. The extant literature is replete with studies that conclude that green buildings, which are a proxy for sustainable real estate, command a green premium, notwithstanding disagreement about the size of the green premium. We revisit the green premium debate by analyzing Building Research Establishment Environmental Assessment Method (BREEAM) certified office buildings (a proxy for green buildings) in the Greater London area to ascertain the prevalence of a green premium and to answer the following questions: is the premium truly green (green-magic)? What prognosis does the green premium provide for sustainability? The study uses quantitative analysis (a hedonic model to analyze 2, 842 CoStar transaction data points from 2008 to 2018 inclusive) and psychographic analysis based on primary data from a questionnaire survey of approximately 450 BREEAM certified building owners and occupiers in the Greater London area to address the research questions. The preliminary results of the hedonic model analysis show that BREEAM certification commands a rental and price premium of 4.3% and 22.3% respectively. Furthermore, the results reveal that a higher certification level generally generates a higher premium while certified buildings in outer zones generate a higher premium than those in the CBD. In addition, the results of both the quantitative and psychographic analyses imply that the premium is more a novelty premium than green-magic. This portends a dismal prognosis for sustainability and warns that sustainability cannot be won on purely economic grounds. Finally, the results of the psychographic analyses show that there is no meeting of minds ( consensus ad idem) between investors in green office buildings on one side and green office space users (tenants) on the other. The results of the study could be of interest to London green office building market participants, researchers, practitioners, and sustainability adherents.